Is the Karyotype of Neotropical Boid Snakes Really Conserved? Cytotaxonomy, Chromosomal Rearrangements and Karyotype Organization in the Boidae Family. - Patrik F Viana; Leila B Ribeiro; George Myller Souza; Hipócrates de Menezes Chalkidis; Maria Claudia Gross; Eliana Feldberg (PLoS ONE, 2016)
Boids are primitive snakes from a basal lineage that is widely distributed in Neotropical region. Many of these species are both morphologically and biogeographically divergent, and the relationship among some species remains uncertain even with evolutionary and phylogenetic studies being proposed for the group. For a better understanding of the evolutionary relationship between these snakes, we cytogenetically analysed 7 species and 3 subspecies of Neotropical snakes from the Boidae family using different chromosomal markers. The karyotypes of Boa constrictor occidentalis, Corallus hortulanus, Eunectes notaeus, Epicrates cenchria and Epicrates assisi are presented here for the first time with the redescriptions of the karyotypes of Boa constrictor constrictor, B. c. amarali, Eunectes murinus and Epicrates crassus. The three subspecies of Boa, two species of Eunectes and three species of Epicrates exhibit 2n = 36 chromosomes. In contrast, C. hortulanus presented a totally different karyotype composition for the Boidae family, showing 2n = 40 chromosomes with a greater number of macrochromosomes. Furthermore, chromosomal mapping of telomeric sequences revealed the presence of interstitial telomeric sites (ITSs) on many chromosomes in addition to the terminal markings on all chromosomes of all taxa analysed, with the exception of E. notaeus. Thus, we demonstrate that the karyotypes of these snakes are not as highly conserved as previously thought. Moreover, we provide an overview of the current cytotaxonomy of the group.